Возбуждаемые усилия в инструменте с прямым пропусканием тока для рихтовки кузовных панелей автомобилей - Волонцевич, Дмитрий Олегович; Аргун, Щасяна Валиковна (НТУ "ХПИ", 2015)
Работа посвящена численным оценкам влияния ширины распределения токов в электродинамических инструментах, которые предназначены для рихтовки металлических обшивок автомобильных кузовов. Полученные оценки позволяют связать геометрию конструктивных составляющих инструмента с глубиной устраняемой вмятины в смысле эффективности силового воздействия. Данные оценки определяют рекомендации по выбору основных параметров электродинамического инструмента рихтовки для устранения вмятин соответствующего размера с кузовной панели автомобиля.

The work is devoted to numerical assessments of the impact of the width of the distribution of currents in the electrodynamics instruments straightening metal plating of automobile bodies. Those tools allow for restoration of the damage (dents) on the surface outside the automobile body without disassembling. The largest value force takes place at a sufficiently small transverse size distribution of currents flowing. The estimates obtained allow us to link the geometry of the structural make up of existing tool with depth fixed dents in the sense of the effectiveness of force. These assessments determine recommendations on the choice of the main parameters of electrodynamics’ straightening tool for removing dents suitable size with the vehicle body panel. This article shows that the force of gravity decreases with increasing width of the conditional distribution of the current.
Excited by the efforts of the tool with direct transmission of power to the straightening of body panels of cars
Keywords: магнитно-импульсная рихтовка; электромагнитная сила притяжения; ремонтные технологии; удаление вмятин; electromagnetic-pulse forming; electromagnetic attractive force; repair technologies; dent removing